Polyelectrolyte: Science and Application - Akyol, Emel; Kirboga, Semra; Oner, Mualla (SPRINGER-VERLAG BERLIN, 2014)
Polyelectrolytes, which are a macromolecule dissolved in water or polar solvent, have gained a wide attention among scientists and engineers for their wide application areas. Their different properties have allowed them to be used in many areas such as soap, body lotions, electrochromic devices, solid-state reference electrode systems, fuel cell exchange membranes, water treatment, waste treatment, paper production, corrosion protection, fuel cells, electrodialysis, contact lenses, membrane-based separations, drug delivery, and genetic science. Biocompatible polyelectrolytes are also utilized in biosensors and biomolecular recognition systems. Layer-by-layer (LbL) technique can be used to produce polyelectrolyte multilayer. Severe substrate such as gold, quartz, silicon, glass, plastic, stainless steel can be used in LbL technique. LbL technique is reproducible, cost-effective, and environmentally-friendly method. The characteristic properties of polyelectrolyte depend on the interaction between electrostatic forces. The degree of polymer charge can modify the electrostatic interactions. We examine the scaling theory according to Gennes et al. and Beurle and Nogovitsin in this chapter. After having discussed the scaling theory, we provide a basic introduction to properties of the neutron scattering and dynamic light scattering. In the end, we analyzed biopolymers and ionomers briefly. Polyelectrolytes (PEs) are generally defined as macromolecules, which when dissolved in water, dissociate to give highly charged polymeric molecules [1-3]. As another definition, polyelectrolytes are polymers carrying either positively or negatively charged ionizable groups. These groups dissociate under appropriate conditions, and leaving ions on the chain and counter ions in the solution Examples of polyelectrolytes include polystyrene sulfonate, polyacrylic and polymethacrylic acids and their salts. DNA, proteins, nucleic acids, polysaccharides and other polyacids are given example to the natural polyelectrolytes [4-8]. Polyelectrolytes are well known to play a vital role in nature and technology. PEs finds widespread use as solubilizing agents, phase separation agents, and rheological property modifiers in daily life and technological applications. However, despite of their fundamental and practice importance, PEs systems still remain only poorly understood. This relates to the fact that their chemistry and physics are influenced by many controlling parameters, such as molecular weight, salt concentration, pH of the solution, etc. [9, 10].
Keywords: NEUTRON-SCATTERING; DIELECTRIC-PROPERTIES; PERSISTENCE LENGTH; SCALING THEORY; INHIBITION; CRYSTALLIZATION; BIOPOLYMERS; ACID; DYNAMICS; COLLAPSE; Thermodynamics; Materials Science